Identifying the resonance curve of a system subjected to linear and quadratic parametric excitations (case with damping) - Nguyen Van Dinh; Tran Kim Chi (Vietnam Journal of Mechanics)
In [3], a quasi linear oscillating system simultaneously subjected to linear and cubic parametric excitations has been studied. In the present paper, we examine the case in which the linear and quadratic parametric excitations are present.